Analysis of the Current Situation of Credit Investigation Management in China - Moying, Li (Pacific International Journal, 2024)
This study provides a comprehensive analysis of credit investigation management in China, emphasizing its significance in building a social credit system and promoting national development. The literature review highlights the evolution of credit investigation in the era of big data, focusing on the integration of cloud computing, artificial intelligence, and blockchain technologies to enhance credit evaluation accuracy and efficiency. The research employs literature research, case analysis, and factor analysis methods to explore the current state and challenges of credit investigation management in Chinese universities. The study identifies the theoretical value of big data in credit investigation and underscores the importance of data governance. It also examines the origin and development of credit investigation management as a discipline, offering insights into curriculum design in universities. The findings reveal that while credit management education in China faces challenges, there are significant opportunities for growth and development. The study concludes with recommendations for strengthening research, standardizing courses, and investing in teaching resources to improve credit management education.